Task analysis of semantic verbal fluency in people diagnosed with Alzheimer’s disease and healthy adults - Horcajuelo, Claudia; Criado-Álvarez, Juan José; Correa, Silvia; Romo, Carmen (Revista de Investigación en Logopedia, 2014)
Memory is one of the most complex human brain capacities and their alteration causes functional impairment disorders. It is divided by temporary and by content. Alzheimer’s disease is the most common type of dementia and it is a disease that causes deterioration in neuropsychological functioning. Furthermore, it contributes between 60% and 70% of dementia cases each year and 7.7 million new cases are recorded. This disease is divided into three stages: initial, intermediate phase and terminal phase. Verbal fluency is defined as a task of language production that involves implementation of mechanisms for lexical access. The objective is to determine whether there is impairment in semantic verbal fluency comparing subjects with Alzheimer’s disease and control subjects. We evaluated a total of 29 patients and it was applied a test that evaluates the semantic verbal fluency called "set test Isaac", consists of four semantic categories (colors, cities, animals and fruits). The analysis of the results shows significant difference between two groups and the validity of the test. Semantic fluency may be affected in people diagnosed with Alzheimer’s disease. Isaac set test was a valid test to discriminate semantic verbal fluency in patients with Alzheimer’s disease and control group.